Strategi Guru Dalam Mengembangkan Kreativitas Anak Melalui Metode Eksperimen Di Pos Paud Mawar Tlogojati Kabupaten Wonosobo - Maulida Rahma Susanti; Kesuna Hilyati Fadhila; Hidayatu Munawaroh (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
One important aspect that needs to be developed through early childhood education is creativity. To be able to develop children's creativity optimally, teachers need the right strategy. One strategy that teachers can use to develop children's creativity is to use the experimental method. Through experimentation, children can discover new ideas or new works that they have never encountered before. This research aims to determine teachers' strategies in developing children's creativity through experimental methods at the Mawar Tlogojati PAUD Post, Wonosobo Regency. The methodology in this research uses qualitative research with descriptive qualitative research type. Based on the research that has been carried out, the research results show that the strategy used by teachers to develop children's creativity through experimental methods is to carry out simple experiments on Swimming Eggs, Magic Colors, Rainbow Rain, Rain Replicas, Piu (Air Fire) Experiments. Through these experimental activities, children's creativity has developed quite well. The research results, shown through indicators of children's creative achievements, showed that 1 child was in the BSB stage, 4 children were in the BSH stage, 2 children were starting to develop (MB), and 2 children were not yet developing (BB). Supporting factors for teachers in efforts to develop children's creativity through experimental methods include a safe and comfortable environment around children and teacher creativity in carrying out learning. Meanwhile, the inhibiting factors are the children's parents who still intervene too much during the learning process, as well as the lack of facilities and infrastructure that support the development of children's creativity.